Konsumsi ikan bersifat protektif terhadap diagnosis stroke pada orang yang pernah terdiagnosis hipertensi di Indonesia - Arif Rahmat Kurnia; Martalena Br. Purba; I Made Alit Gunawan (Jurnal Gizi Klinik Indonesia, 2018)
Background: Stroke is a burdensome disease. The prevalence of stroke has increased by 16% over the last 6 years. The biggest risk factor for stroke is hypertension, but consumption of animal products such as meat, fish, eggs, and milk is often associated with the onset of stroke.Objective: To examine the relationship between the frequencies of animal products consumption to the incidence of stroke in 2014/2015 on hypertensive people in 2007/2008.Method: This research was using case control design performed by analyzing longitudinal data derived from Indonesian Family Life Survey (IFLS) 4 and 5 (2007/2008 and 2014/2015). The population of this study was Indonesian aged over 40 years who have been diagnosed with hypertension in IFLS 4.Results: The results of bivariate analysis using Chi Square test and Fisher's exact test found that the variables significantly associated with stroke diagnosis in IFLS 5 were IFLS 5 fish consumption (p=0.027; OR=0.47); IFLS 4 milk consumption (p=0.04; OR=2.97); IFLS 5 hypertension diagnosis (p=0.006; OR=4.03); IFLS 4 diabetes mellitus diagnosis (p=0.033;OR=8.91); and IFLS 5 diabetes mellitus diagnosis (p=0.041; OR=3.73), also IFLS 5 physical activity (p=0.00; OR=0.34).Conclusion: Fish consumption of 2 - 7 days per week and adequate physical activity is associated with a decreased risk of stroke in a population that has been diagnosed with hypertension. Daily milk consumption, hypertension diagnosis, and diabetes mellitus diagnosis may increase the risk of stroke.